Power, Gender, and Canon Formation in Mexico - Cynthia Steele (Studies in 20th & 21st Century Literature, 1996)
I propose to analyze Castellanos's trajectory from marginalized ethnographer and critic of "latino" society, to presidential insider and ambassador, and the first modern Mexican woman writer to be accepted into the literary canon. I will explore the intersection of politics, gender, and the (self-) creation of a literary persona with regard to the following issues: 1) the tension between self-exposure and self-censorship in Castellanos's literary work; 2) Castellanos's intense and problematic relationship with her illegitimate, mestizo half-brother; 3) the coincidences and contradictions between Castellanos's journalistic account of her relationship with her servant Maria Escandon, and Maria's own oral history twenty years later; 4) the tension between depression and dependency, on the one hand, and self-assertiveness and audacity, on the other; 5) the relation between Castellanos's role as ambassador and the personal, apolitical, often frivolous character of her journalistic articles written in Israel; 6) the contradictory readings of Castellanos's death, and the respective implications for her place in the canon; and 7) the implications, for their reception, of the love letters published in Cartas a Ricardo 1994, as opposed to 1974.
Keywords: power; gender; Castellano; marginalization; latino society; Mexican women writer; women; politics; self; self creation; mestizo; Cartas a Ricardo